The Development of Local Wisdom-Based Physics Cognitive Ability Assessment Instrument for Senior High School Students - Anggraeni, Tyas Endah; Mundilarto, Mundilarto (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2020)
Today's young generation hardly recognizes the values of local wisdom around them. That is because of their lack of curiosity towards wisdom itself and the lack of means to learn it. Therefore, local wisdom needs to be integrated with learning particularly in high schools, especially in Klaten Regency. This study aims to develop an instrument of cognitive ability assessment based on local wisdom and find out its validity and reliability. The development of the assessment instrument refers to the instrument development model by Oriondo and Dallo-Antonio which is divided into 4 stages: designing the instrument, determining the validity of the instrument, testing the instrument, and determining the reliability of the instrument. The instrument was validated by educational evaluation experts, physicists, physics education experts, and practitioners. The content validity of the instrument was analyzed using the V-Aiken formula. The instrument consisted of 50 valid items based on expert judgment with an average coefficient of V-Aiken>0.78. Researchers tested 480 students and then analyzed the results of the trials using the Microsoft Excel, Quest, Parscale to determine their validity and reliability. The analysis showed that 50 items were fit with the Partial Credit Model (PCM). The reliability results showed 0.82.